DESIGN OF DRAINAGE SYSTEM IN SUGAR FACTORY AREA PT. REJOSO MANIS INDO, BLITAR REGENCY, EAST JAVA - Maulana Ichsan, Diki
Sugar factory of PT. Rejoso Manis Indo was built on an area of 20.1 ha in village of rejoso, sub-district of binangun, blitar regency, east java. Design of drainage system in the area is determined based on the return periode of the rainfall. For drainage system have a return period is 10 years and for the river floods is 50 years using the Log Pearson III distribution method. For determined of river floods was obtained using ITB-2 method for rejoso with discharge value is 186.48 m3/s and sambigede using nakayasu method with discharge value is 220.23 m3/s. Based on the river modeling performed, obtained the water level elevation of flood in rejoso is +208.80 m. In the design of the drainage system there are 4 catchements and the each catchements have some sub-catchements. The cross section of the drainage channel is square and the material was built in U-Ditch precast concrete that is available on the market and the dimension is calculated based on flood discharge using rational method. Then doing the hydraulic simulations using the SWMM program to know the water level and discharge on the each channels. The drainage pool was designed to be able accommodate for the first of 3 hours rainfall. The drianage pools have two pools on this area that is KU and KS for the each dimensions is 85 m x 50 m x 2.5 m and 40 m x 30 m x 2.5 m. The construction of the pool wall uses retaining wall made from split stone pairs materials.